Tumor‐associated lymphocytes and macrophages are related to stromal elastosis and vascular invasion in breast cancer. (2nd June 2021) - Chen, Ying; Klingen, Tor Audun; Aas, Hans; Wik, Elisabeth; Akslen, Lars A
Abstract: The tumor microenvironment plays a critical role in breast cancer progression. Here, we investigated tumor‐infiltrating lymphocytes (TILs) and associations with macrophage numbers, tumor stromal elastosis, vascular invasion, and tumor detection mode. We performed a population‐based retrospective study using data from The Norwegian Breast Cancer Screening Program in Vestfold County (2004–2009), including 200 screen‐detected and 82 interval cancers. The number of TILs (CD45+, CD3+, CD4+, CD8+, and FOXP3+) and tumor‐associated macrophages (CD163+) was counted using immunohistochemistry on tissue microarray slides. Lymphatic and blood vessel invasion (LVI and BVI) were recorded using D2‐40 and CD31 staining, and the amount of elastosis (high/low) was determined on regular HE‐stained slides. High numbers of all TIL subsets were associated with LVI ( p  ≤ 0.04 for all), and high counts of several TIL subgroups (CD8+, CD45+, and FOXP3+) were associated with BVI ( p  ≤ 0.04 for all). Increased levels of all TIL subsets, except CD4+, were associated with estrogen receptor‐negative tumors ( p  < 0.001) and high tumor cell proliferation by Ki67 ( p  < 0.001). Furthermore, high levels of all TIL subsets were associated with high macrophage counts ( p  < 0.001) and low‐grade stromal elastosis ( p  ≤ 0.02). High counts of CD3+, CD8+, and FOXP3+ TILs were associated with interval detected tumors ( p  ≤ 0.04 for all). Finally, in the luminal A subgroup, high levels of CD3+ and FOXP3+ TILs were associated with shorter recurrence‐free survival, and high counts of FOXP3+ were linked to reduced breast cancer‐specific survival. In conclusion, higher levels of different TIL subsets were associated with stromal features such as high macrophage counts (CD163+), presence of vascular invasion, absence of stromal elastosis, as well as increased tumor cell proliferation and interval detection mode. Our findings support a link between immune cells and vascular invasion in more aggressive breast cancer. Notably, presence of TIL subsets showed prognostic value within the luminal A category.